(untitled) (RUNA, archivo para las ciencias del hombre, 2015)
Evaluadores Nacionales • Carolina Alvarez Avila – Universidad Nacional de Córdoba • Silvia Balzano – Pontificia Universidad Católica Argentina • Natalia Castelnuovo – Universidad Nacional de San Martín • Andrés Dapuez – Universidad Nacional de Entre Ríos • Mariano Carlos Del Papa – Universidad Nacional de La Plata • María Laura Diez – Universidad de Buenos Aires • Mariana Fabra – Universidad Nacional de Córdoba • Claudia Figari – CEIL - CONICET • Valeria Hernández – Universidad Nacional de San Matrín • Carina Jofre – Universidad Nacional de San Juan • Mario Lattuada – Universidad Nacional de Rosario • Mariana Lorenzetti – Universidad de Buenos Aires • María Inés Poduje – Universidad Nacional de La Pampa • Pablo Schamber – Universidad Nacional de Lanús • Héctor Vázquez – Universidad Nacional de Rosario • Areli Veloz Contreras – Universidad Nacional de San Matrín Evaluadores Extranjeros • Jean Pierre Bastian – Universidad Marc Bloch Estrasburgo, Francia • Alinne Bonetti – Universidad Federal do Pampa (Unipampa), Brasil • Luis Cayòn – Universidad de Brasilia, Brasil • Jean Langdon – Universidad Federal de Santa Catarina, Brasil • María Clara Medina – Universidad de Göterborg, Suecia • Diana Mulinari – Lund University, Suecia • Flávio Braune Wiik – Universidad Estadual de Londrina, Brasil